Worldwide asthma epidemiology: insights from the Global Health Data Exchange database. Issue 1 (23rd October 2019) - Mattiuzzi, Camilla; Lippi, Giuseppe
Abstract : Background: Enhanced focus on primary care provision is essential for lowering the risk of asthma exacerbation and complications, as well as for decreasing asthma‐related hospitalizations and deaths. This article provides an update on current worldwide epidemiology of asthma. Methods: Worldwide epidemiologic information on asthma was obtained through electronic searches in the Global Health Data Exchange (GHDx) database. Results: In 2017, the incidence of asthma was 43.12 million new cases/year (0.56%), while in that same year, prevalence and mortality accounted for 272.68 million cases (3.57%) and 0.49 million deaths (0.006%), respectively. Although the number of asthma cases significantly increased during the last 25 years, disability‐adjusted life years (DALYs) and deaths constantly declined. After adjustment of asthma incidence, prevalence, and DALYs for worldwide demographic variation, no significant changes could be seen during the last 25 years, while asthma mortality significantly declined during the same period. Asthma incidence peaks before the age of 5 years, whereas prevalence and DALYs peaks are observed between 0 and 14 years. DALYs also display a second peak, between 45 and 74 years. Asthma mortality increases with aging, reaching the peak after 80 years. The epidemiologic burden and mortality of asthma are constantly higher in women than in men. An inverse, highly significant correlation can be found between sociodemographic index and asthma incidence ( r = −0.98) or mortality ( r = −0.96). Conclusion: Although the worldwide burden of asthma remains high, incidence and prevalence are not apparently translating into an escalating clinical and economic burden in terms of health loss and deaths.